2014
DOI: 10.1515/cclm-2014-0224
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding prevalence and transfusion requirement in patients with thrombocytopenia in the emergency department

Abstract: Background: Thrombocytopenia is the most common coagulation disorder in critically ill patients. No studies have investigated the epidemiology and clinical impact of this condition in emergency department (ED) patients. We aimed to investigate epidemiological features, incidence of bleeding, and diagnostic and therapeutic requirements of patients with thrombocytopenia admitted to the ED. Methods: We performed a retrospective observational study enrolling all patients admitted to the medical-surgical ED of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Thrombocytopenia, traditionally defined as a platelet count less than 150 9 10 9 /L, is a common haematological alteration in critical illness [3]. In patients with sepsis, thrombocytopenia is associated with a higher vasopressor requirement and a lower PaO 2 /FiO 2 ratio [4].…”
Section: Platelet Concentrationmentioning
confidence: 99%
“…Thrombocytopenia, traditionally defined as a platelet count less than 150 9 10 9 /L, is a common haematological alteration in critical illness [3]. In patients with sepsis, thrombocytopenia is associated with a higher vasopressor requirement and a lower PaO 2 /FiO 2 ratio [4].…”
Section: Platelet Concentrationmentioning
confidence: 99%
“…Primary thrombocytopenia is usually found in chronic diseases of the blood system, while acquired thrombocytopenia is found in infections, trauma, surgery, drugs, radiotherapy, immune dysfunction, and nutritional disorders. A study of emergency-related thrombocytopenia showed that its main causes included liver cirrhosis, hematological tumors, chemotherapy-induced thrombocytopenia (CIT), disseminated intravascular coagulation (DIC), infection, and drug-mediated thrombocytopenia ( Turvani et al, 2014 ). Infection is one of the causes of thrombocytopenia, in which platelets are mobilized to the blood vessel wall in an inflammatory response, interacting with white blood cells, allowing leukemia to aggregate to the site of inflammation, appearing to plug fissures in the blood vessel wall, and helping to maintain the integrity of blood vessels ( Ho-Tin-Noé et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%